Kebijakan Hukum Mengenai Pengawasan oleh Dewan Pengawas Otoritas Jasa Keuangan - Sandhi Bagus Permana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The establishment of the OJK Supervisory Board (SB of OJK), as mandated by Law Number 4 Year 2023 concerning the Development and Strengthening of the Financial Sector (Law Number 4/2023), is intended to assist the House of Representatives (DPR) in overseeing OJK while also opening space for public participation by enabling the submission of reports and/or inputs regarding OJK’s institutional performance. By employing a normative juridical research method, this study seeks to illustrate the political and legal context in Indonesia underlying the formation of SB of OJK, as well as the implications for OJK’s independence